Reserva de cargos e empregos públicos a pessoas com deficiência: instituições federais de ensino no RN - Maia, Deliany Vieira de Alencar (2014)
With a focus on the need for effectiveness of fundamental rights of persons with disabilities, this dissertation held a scientific research to analyze the degree of implementation of reservation of positions and public jobs to people with disabilities in the Brazilian State, because the 1988 Federal Constitution expressly determined such a reservation in your article 37, VIII. Highlight that this subject is enough evidence, given the large number of open public competition in recent years in Brazil, as well as recent proposals to grant equal rights to blacks (Bill nº 6,738/2013). In addition, the wording the constitutional device comes fomenting heated discussions on the subject, which are flowing on the doors of the judiciary and are spicy because such protection Microsystem vulnerable group has several gaps in the regulation of this policy. However, the research produced, unlike other related theme, does not address the problem of inefficiency in its constitutional theory, that is, abstractly, but also focuses on a specific analysis of this ineffectiveness within Brazilian society, so that research based on a bibliographical analysis, plus a study case law, at the national level, as well as in field research, while case study, focusing on the technique of the analysis of everyday life, because it was believed that the degree of realization of the constitutional norm debated is not yet a satisfactory degree of effectiveness. Soon, the methodological procedures chosen confirmed such a hypothesis and contributed to the study of realization of the fundamental right to work of people with disabilities in Brazil, the light of a Constitutional State, proposing a constitutionally appropriate model the greater effectiveness of the constitutional norm studied